Operation optimization study of water pump production model based on low-carbon economy concept - Xu, Jing; Lu, Yixuan (Frontiers in Energy Research, 2023)
The inventory and delivery rate of water pump are affected largely by the production mode. In order to improve the operation optimization of water pump production model, the simulation test method and system dynamics model were selected in the manuscript. Three different production modes, namely traditional make-to-order (MTO) model, make-to-stock (MTS) mode, and MTO & MTS model, were compared in terms of the indicators such as the inventory, productivity and delivery rate of water pump. Moreover, the three above production modes were also assessed by using the fuzzy comprehensive evaluation method. The results show that it is not well adapted in practical applications for the MTS production model with an intermediate level of inventory and customer demand satisfaction. The MTO production model is appropriate when it’s easy to predict the customer demand that fluctuates scarcely. The MTO & MTS production model should be selected when it’s difficult to predict the customer demand that fluctuates sharply. After comprehensive evaluation, the MTO & MTS production model is the best choice for pump.